Family History of Colorectal Cancer: Clinicians' Preventive Recommendations and Patient Behavior - Zlot, Amy I. (Centers for Disease Control and Prevention, 2011)
Few population-based studies have addressed the role that family history of colorectal cancer (CRC) plays in clinician decision making or patient health choices. The objective of this study was to evaluate the effect of family history of CRC on clinician practice, patient CRC screening, and patient preventive behavior. We analyzed 2008 Oregon Behavioral Risk Factor Surveillance System data to examine associations between family history of CRC and 1) patient-reported clinician recommendations, 2) perceived risk of developing CRC, 3) adoption of preventive and screening behaviors, and 4) CRC risk factors among 1,795 respondents without CRC. A family history of CRC was positively associated with a higher likelihood of respondents reporting that their clinicians discussed colorectal cancer screening (OR, 4.2; 95% CI, 2.4-7.4) and of respondents having colorectal screening within the recommended time period (OR, 2.2; 95% CI, 1.3-3.9). A family history of CRC was also associated with respondents reporting lifestyle changes to prevent CRC (OR, 2.6; 95% CI, 1.7-4.0). A family history of CRC may prompt clinicians to recommend screening and preventive behavior changes and motivate patients to adopt such strategies.